Duodenal web resection via hybrid natural orifice transluminal endoscopic surgery (NOTES) - Maria Carmen Mora; Gregory T. Banever; Michael V. Tirabassi; Kevin P. Moriarty (Elsevier, 2015)
Congenital duodenal atresia, stenosis, and webs are a common cause of proximal obstruction in the newborn period. A variety of surgical techniques have been described for the treatment of duodenal webs. Open and laparoscopic duodenotomy with web resection have been well described; endoscopic resection has also shown to have promising success. We describe a case of a 2-year-old male with a duodenal web, which was resected via an existing gastrostomy site utilizing a modified hybrid natural orifice transluminal endoscopic surgery (NOTES).